Impact of chronic heat stress on behavior, oxidative status and meat quality traits of fast-growing broiler chickens - Cartoni Mancinelli, Alice; Baldi, Giulia; Soglia, Francesca; Mattioli, Simona; Sirri, Federico; Petracci, Massimiliano; Castellini, Cesare; Zampiga, Marco (Frontiers in Physiology, 2023)
This research aimed to investigate, through a multifactorial approach, the relationship among some in-vivo parameters (i.e., behavior and blood traits) in broilers exposed to chronic HS, and their implications on proximate composition, technological properties, and oxidative stability of breast meat. A total of 300 Ross 308 male chickens were exposed, from 35 to 41 d of age, to either thermoneutral conditions (TNT group: 20°C; six replicates of 25 birds/each) or elevated ambient temperature (HS group: 24 h/d at 30°C; six replicates of 25 birds/each). In order to deal with thermal stress, HS chickens firstly varied the frequency of some behaviors that are normally expressed also in physiological conditions (i.e., increasing "drinking" and decreasing "feeding") and then exhibited a behavioral pattern finalized at dissipating heat, primarily represented by “roosting”, "panting" and "elevating wings". Such modifications become evident when the temperature reached 25°C, while the behavioral frequencies tended to stabilize at 27°C with no further substantial changes over the 6 d of thermal challenge. The multifactorial approach highlighted that these behavioral changes were associated with oxidative and inflammatory status as indicated by lower blood γ-tocopherol and higher carbonyls level (0.38 vs. 0.18 nmol/mL, and 2.39 vs. 7.19 nmol/mg proteins, respectively for TNT and HS; P<0.001). HS affected breast meat quality by reducing the moisture:protein ratio (3.17 vs. 3.01, respectively for TNT and HS; P<0.05) as well as the muscular acidification (ultimate pH = 5.81 vs. 6.00, respectively; P<0.01), resulting in meat with higher holding capacity and tenderness. HS conditions reduced thiobarbituric acid reactive substances (TBARS) concentration in the breast meat while increased protein oxidation. Overall results evidenced a dynamic response of broiler chickens to HS exposure that induced behavioral and physiological modifications strictly linked to alterations of blood parameters and meat quality characteristics.